Art and Worship in the Insular World
1 online resource.
Keywords: A monastic artist with an unusual enthusiasm of male buttocks and genitalia; a nun bringing her spinning equipment from her home in the south to her new convent in the north; the riddle of a carved archer bearing a book instead of arrows; a bishop's ring hiding in its design symbols of the essential aspects of the Christian faith: these are some of the secrets of early medieval personal and public worship uncovered in this book. In tribute to a scholar who is herself a polymath of early medieval studies, these chapters explore approaches which have particularly engaged her: stone sculpture; text; textiles; manuscript art; metalwork; and archaeology. With a brief foreword by Professor Dame Rosemary Cramp. Contributors are Richard N. Bailey, Michelle P. Brown, Peter Furniss, Jane Hawkes, David A. Hinton, Maren Clegg Hyer, Catherine E. Karkov, Alexandra Lester-Makin, Christina Lee, Donncha MacGabhann, Éamonn Ó Carragáin, Gale R. Owen-Crocker, Frances Pritchard, and Penelope Walton Rogers.